Penambahan Ampas Sagu Terfermentasi (Metroxylon sago) Terhadap Performa Ayam Kampung Super Fase Starter - Ahmad - Sudarto; Fahria Datau; Suparmin Fathan (Jambura Journal of Animal Science, 2021)
This study aims to determine the performance of super native chickens fed with fermented sago dregs as a substitute for corn in the ration. Super native chickens used in the study were 80 chickens. The research design used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatment in this study was P0 (without a mixture of fermented sago dregs), P1 (rations with an additional 10% fermented sago dregs), P2 (rations with an additional 20% fermented sago dregs), P3 (rations with an additional 30% fermented sago dregs). The variables observed were ration consumption, body weight gain and ration conversion. Based on the analysis of variance, it showed that dietary consumption was not significantly differed (P0,05), while body  weight gain and diet conversion were significantly differed (P0,01). Therefore, the use of fermented sago dregs in the ration of super native  chickens can significantly affect body weight gain and ration conversion up to the level of 20%.